Dialogias no Vale do Amanhecer: os signos de um imaginário religioso antropofágico - Cavalcante, Carmen Luisa Chaves (2005)
The following study is the result of an investigation about some of the model vectors that took place at "Dawn Valley" - a religious community founded in 1968 by former truck driver Neiva Chaves Zelaya, and that is six kilometers far from Planaltina, a sattelite city of Brasília. Here we support the idea that as the city of Brasilia and all the new age misticism wave tied to it as well; the popular catholicism, the kardecist spiritism and the "umbanda"; also the traditional communication means, such as the cinema, the television, the best-seller books, among others; all together dialogue with the Valley and fundamentally play a role in its signal composition. These are the dialogues which, under the perspective of the semiotic of Russian extraction, also known as the semiotic of the culture, the following work will seek for. Everything is to think over the aspects concerning the attendance existence, in that community, of information linked to outer planet beings and their spaceships; the Egyptian civilization with its pyramids and faraohs; as well as the Brazilian Indigenous, North-American, and pre-Colombian peoples cultures, mainly the Inca, Maya, and Aztec - so be the information in the mithic narratives, in the rituals, in the iconography, or in the garment of the adepts. Information that, right after getting at the Valley, turned into a re-signification, and thus was modified there. The information found there is under the drums of a signal anthropofagy, presenting before anything else, a semiosic newness. Something that was remarkably chewed and swallowed by that community, so that after digestion, might it go back to the scene as pure creation. In an attempt of holding all the consideration gama, we decided to divide the thesis in five chapters, remarkably interlinked. Here they are: "Mistic Brasília: A Planet Different from Earth"; "Dawn Valley: a 'Soul' to the Modern City"; "The Valley, the Notion of Science and the Spaceships"; "Egypt and Dawn Valley" and, at last, "An Indigenous Dawn Valley".